Facilitating Staff Involvement in Implementing Appropriate Interventions - Catterall, Calvin D. (Canadian Journal of Counselling and Psychotherapy, 2012)
The need for a Learning Facilitation Team is described which cooperatively works to find solutions for the problems presented by specific students. The team is also charged with the responsibility of encouraging total staff involvement by directing their attention to a series of questions in the four major areas available to schools to help students: Developing Academic Intellectual Skills, Utilizing Corrective/Remedial Interventions, Developing Life Skills, and Utilizing Corrective/Therapeutic Interventions. Based on this information the team is encouraged to build a total school plan for helping students based on: the interpersonal relations ofthe staff, the availability of manpower needed to get the job done, and the procedures established to work with students with special needs.